Improving Inventory of Organization by System Dynamics Analysis - Don Pan, Bing (International journal of industrial engineering and operational research, 2022)
Inventory management is a crucial aspect of any organization, as it directly impacts the profitability and sustainability of the business. In this paper, we explore the use of system dynamics analysis to improve inventory management in organizations. We begin by providing an introduction to the concept of inventory management and its importance in organizational success. We then review the existing literature on inventory management and system dynamics analysis, highlighting the benefits and limitations of these approaches. Next, we describe our methodology for conducting a system dynamics analysis of inventory management in an organization. We present our numerical results, which demonstrate the effectiveness of our approach in improving inventory management. Finally, we conclude by discussing the implications of our findings and suggesting future research directions.